Peran Bahasa Indonesia dalam Mengkomunikasikan Nilai-Nilai Islam pada Tradisi Lampung - Palyanti, Mega; Sinta Bela; Ayu Wulandari; Dea Olivia; Nopita Sari (Bulletin of Community Engagement, 2024)
This research is motivated by the important role of the Indonesian language in spreading Islamic teachings and values in Lampung customs and traditions. Indonesian, as the main means of communication, has a great influence in the lives of people of diverse ethnicity and regional languages. The research method used is a literature study with a qualitative approach, looking for sources from scientific journals, books, and news from media such as social media, television, and newspaper media. The results show that the Indonesian language is important in improving the understanding of Islamic values in Lampung traditions. The use of Indonesian facilitates the wider dissemination of Islamic values and fosters a stronger relationship between Islamic teachings and local culture, overcoming the difficulties of communication between ethnicity and regional languages, and strengthening Lampung's customary traditions within the framework of Islamic teachings.